2014
DOI: 10.14214/df.172
|View full text |Cite
|
Sign up to set email alerts
|

In search of sustainable competitive advantage in the wood products industry: Evidence from China and Finland

Abstract: Given the dramatic changes such as globalization, increasing energy costs, technology development and climate change that are occurring in the global business environment, the wood products industry faces the challenges of rising production costs, rapid technology transfer and increasing corporate environmentalism. Consequently, the traditional sources of competitive advantage based on economies of scale are no longer sufficient in today's highly competitive and dynamic market. Implementing a purely convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the government, industrial associations, and companies should take initiative measures to promote Chinese companies and transform them from the main equipment manufacturers to the main design and branding manufacturers. Wan (2014) investigated the sources of sustainable competitive advantage and the corresponding changes in competitive strategy in the wood products industry in China and Finland. The results show a growing trend in product-to-market transition and stakeholder orientation from cost leadership to differentiation strategy and from low-value-added products to high-value-added products in both countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the government, industrial associations, and companies should take initiative measures to promote Chinese companies and transform them from the main equipment manufacturers to the main design and branding manufacturers. Wan (2014) investigated the sources of sustainable competitive advantage and the corresponding changes in competitive strategy in the wood products industry in China and Finland. The results show a growing trend in product-to-market transition and stakeholder orientation from cost leadership to differentiation strategy and from low-value-added products to high-value-added products in both countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has also suggested that the wood products industry should be "like any other high-end, highly technological, and knowledge-based business" where managers are able to tailor their manufacturing competencies according to their target markets (Spetic et al, 2016, p. 25). The strong emphasis on knowledge utilization (i.e., transforming scattered information into valueadded activity) or service (i.e., using firm resources for the benefit of a customer) has resulted in views where knowledge orientation (Cohen et al, 2001) or service orientation Wan, 2014) are suggested as the next possible paradigms of the forest industry. The term "service" suggests that firms alone do not create value, but instead value derives from collaboration with customers, suppliers, employees and other stakeholders.…”
Section: Evolution Of Business Strategies In the Forest Industrymentioning
confidence: 99%
“…However, its B-to-C business mode differs significantly to the other companies' B-to-B forest business. In general, firms in the forest industry have suffered from over-capacity and low profitability during the 2000s, and strategic changes are needed in the long term to add product value, minimize production costs, and accelerate technological innovations (Uronen 2010;Wan 2014).…”
Section: Internationalization Of the Forest Industry Under Economic Gmentioning
confidence: 99%